2020
DOI: 10.2147/bctt.s276404
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inflammation Mediated Hepcidin-Ferroportin Pathway and Its Therapeutic Window in Breast Cancer</p>

Abstract: Experimental and clinical data strongly support that iron is an essential element which plays a big role in cancer biology. Thus, hepcidin (Hp) and ferroportin (Fpn) are molecules that regulate and maintain the metabolism of iron. A peptide hormone hepcidin limits recycled and stored iron fluxes in macrophage and hepatic hepatocyte, respectively, to the blood stream by promoting degradation of the only iron exporter, Fpn, in the target cells. Moreover, the inflammatory microenvironment of breast cancer and alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 135 publications
(260 reference statements)
0
4
0
Order By: Relevance
“…As revealed by the data extracted from TCGA, the correlation between hepcidin and immune cell content had a significant impact on the OS in patients with KIRC. Several studies have shown that hepcidin-associated immune cell infiltration is involved in the development of cancers ( Shibabaw et al, 2020 ; Fan et al, 2021 ), but renal cancer was never mentioned. In this study, the infiltration of most immune cells was linked with elevated hepcidin levels, including those of macrophages, natural killer T cells, B cells, CD4 + memory CD8 + T cells, mesenchymal stem cells, type 1 T-helper cells, type 2 T-helper cells, and regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As revealed by the data extracted from TCGA, the correlation between hepcidin and immune cell content had a significant impact on the OS in patients with KIRC. Several studies have shown that hepcidin-associated immune cell infiltration is involved in the development of cancers ( Shibabaw et al, 2020 ; Fan et al, 2021 ), but renal cancer was never mentioned. In this study, the infiltration of most immune cells was linked with elevated hepcidin levels, including those of macrophages, natural killer T cells, B cells, CD4 + memory CD8 + T cells, mesenchymal stem cells, type 1 T-helper cells, type 2 T-helper cells, and regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, regulating iron metabolism can be used as an antitumor strategy ( Hsu et al, 2020 ; Lelièvre et al, 2020 ). Hepcidin has also been previously reported to play an important role in digestive system tumors, including colorectal cancer ( Sornjai et al, 2020 ; Colorectal Cancer Cells Ectopically Express Hepcidin to Sequester Iron, 2021 ; Schwartz et al, 2021 ), gastric cancer ( Jakszyn et al, 2017 ), pancreatic cancer ( Toshiyama et al, 2018 ), and hepatocellular carcinoma ( Abd Elmonem et al, 2009 ; Udali et al, 2018 ; Wang et al, 2019 ), as well as in thoracic cancers such as breast cancer ( Blanchette-Farra et al, 2018 ; El-Mahdy et al, 2020 ; Jerzak et al, 2020 ; Shibabaw et al, 2020 ; Blindar et al, 2021 ) and lung cancer ( Chen et al, 2014 ; Fan et al, 2021 ). Collectively, hepcidin appears to play an important role in cancer.…”
Section: Introductionmentioning
confidence: 98%
“…Current clinical trials of hepcidin antagonism are primarily centered around malignancy induced anemia of chronic disease and other hematological disorders, although quinoxaline, a small molecule that prevents degradation of the ferroportin receptor was shown to have in vitro activity against the MCF7 breast cancer cell line [153,158]. Previous work has shown that low hepcidin levels in breast cancer cell lines was of particularly favorable prognosis, which may be related to the concentration of intracellular iron and the creation of ROS, driving cancer progression [65,66]. Furthermore, disruption of intracellular iron signaling also has been shown a useful adjuvant agent to traditional chemotherapy for ovarian and breast cancer [159].…”
Section: Hepcidin Therapymentioning
confidence: 99%
“…Moreover, hepcidin promoter DNA is hyper-methylated in HCC, resulting in its transcriptional repression [ 18 ]. On the other hand, reduced hepatic hepcidin expression was found to be protective against the progression of lung and breast cancer [ 19 ]. Moreover, in patients with breast cancer, hepcidin expression is significantly upregulated in tissues and serum and there is evidence supporting the role of hepcidin in the development of the malignant phenotype and resistance to doxorubicin [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%